λ - Borel and λ - Baire Credibility on Normal Topological Space - Ali, Rasha; Noori F. Al-Mayahi (Al-Qadisiyah Journal of Pure Science, 2021)
In this paper, will be presented the concept of Borel sets and Baire sets on normal topological spaces and locally compact topological spaces as new types of λ – system and study the basic characteristics related to each of them and obtain results related to them.